P.22: Improving Switching Characteristics of Amorphous‐InGaZnO4 Thin‐Film Transistors by Dual‐Gate Driving. Issue 1 (1st July 2013) - Mativenga, Mallory; Geng, Di; Um, Jae Gwang; Seok, Manju; Kang, Dong Han; Jang, Jin; Mruthyunjaya, Ravi K.; Heiler, Gregory N.; Tredwell, Timothy J.
Abstract When the top‐gate and bottom‐gate of a dual‐gate amorphous‐InGaZnO4 (a‐IGZO) thin‐film transistor (TFT) are electrically tied together (dual‐gate driving), drain current (IDS) increases fivefold compared to single‐gate driving (i.e. when driving with either bottom‐gate or top‐gate), resulting in significant enhancement of the driving ability of TFTs for active‐matrix display (AMD) applications. The increase in IDS is attributed to better gate drive, achieved through the formation of two parallel channels; one at the top surface and the other at the bottom surface of the semiconductor.